Analisis Daya Tampung Beban Pencemaran Kali Asem di Sekitar TPST Bantar Gebang dan TPA Sumur Batu - Opy Kurniasari; Lina Aprianti (Bumi Lestari Journal of Environment, 2020)
The amount of waste management, especially in big cities and metropolitan areas, forms the basis for various policies. One of them is the Law of the Republic of Indonesia Number 18 Year 2008 concerning Solid Waste Management which mandates cooperation and partnerships between local governments, business entities, and the community in carrying out waste management. The carrying capacity of the environment should be one of the considerations in the preparation and determination of environmental management and recovery plans. However, in its implementation, the calculation of environmental carrying capacity is not easy. Therefore, planning is not based on environmental capability, but existing conditions, which are likely to have experienced degradation or exceeded carrying capacity. This condition is expected to cause a decrease in the carrying capacity of the environment around the Bantar Gebang TPST and Sumur Batu TPA, one of which is the Kali Asem river. Based on this, it is necessary to analyze the assimilative capacity of Kali Asem pollution around the TPST and TPA. The purpose of this study was to analyze the capacity of Asem River pollution load so that the ability of the environment in the area around TPST Bantargebang, Bekasi City to support the lives of humans and other living things. The results of laboratory analysis showed that at the initial sampling point, Kali Asem was already in a polluted condition which is characterized by high levels of BOD and COD.